Expression of sirtuins in ovarian follicles of postnatal mice. Issue 10 (9th September 2020) - Kong, Deqi; Yao, Guidong; Bai, Yucheng; Yang, Guang; Xu, Ziwen; Kong, Yue; Fan, Huiying; He, Qina; Sun, Yingpu
Abstract: Mammalian ovarian follicular development is an intricate, elaborate, and well‐organized phenomenon regulated by various signaling pathways; however, the underlying mechanism remains unclear. Mammalian sirtuins (sirtuin 1 to sirtuin 7) are a group of NAD + ‐dependent deacetylases implicated in various physiological processes including cell proliferation, apoptosis, cell cycle progression, and insulin signaling. Mammalian ovarian sirtuins have been studied using adult and aged bovine, porcine, and murine models. However, limited information is available regarding their precise expression patterns and the localization of follicle development in mice. This study aimed to assess the dynamic expression and localization of all seven sirtuins in early postnatal mouse ovaries through real‐time polymerase chain reaction analysis and immunohistochemistry, respectively. During postnatal ovarian follicle development, sirtuin 1, sirtuin 4, and sirtuin 6 were downregulated compared with those in 1‐day postnatal mouse ovaries ( p  < .05), indicating that these three sirtuin genes may be markers of follicular development. Combining their localization in granulosa cells through immunohistochemical studies, sirtuin 1, sirtuin 4, and sirtuin 6 are suggested to play negative regulatory roles in mammal ovarian follicular granulosa cell development. Furthermore, we found that sirtuin 2 ( p  < .05) and sirtuin 7 ( p  < .05) mRNA were constantly upregulated relative to sirtuin 1, although limited information is available regarding sirtuin 7. Among all sirtuins in mouse ovaries, sirtuin 1 was relatively and steadily downregulated. Upon sirtuin 1 overexpression in 1‐day postnatal mouse ovaries via sirtuin 1‐harboring adenoviruses in vitro, the emergence of primary follicles was delayed, as was the emergence of secondary follicles in 4‐day postnatal ovaries. Further studies on KGN cell lines reported that interfering with sirtuin 1 expression in granulosa cell significantly affected granulosa cell proliferation and the expression of mitochondrial genes. This study presents the first systemic analysis of dynamic patterns of sirtuin family expression in early postnatal mice ovaries, laying the foundation for further studies on less discussed sirtuin subtypes, such as sirtuin 5 and sirtuin 7. Abstract : This study presents the first systemic analysis of dynamic patterns of sirtuin family expression in early postnatal mice ovaries.